Implementasi Pendidikan Multikultural dalam Pembelajaran Sejarah Islam Kelas VIII SMPN 25 Kota Bengkulu - Darmison Vebi Hipriawan; Moch. Iqbal; Nurniswah Nurniswah (Lembaga Pengembangan Kinerja Dosen, 2026)
The purpose of this research is to look at how eighth graders at SMP Negeri 25 Kota Bengkulu are studying Islamic history through the lens of multicultural education and to find out what problems instructors are having with it. The study used a qualitative methodology, gathering information via in-depth interviews with the principal, homeroom teacher, and social studies instructor. The results show that Islamic history classes have adopted multicultural education techniques by including diversity principles into their lessons and pedagogy. This is shown in the following ways: the importance of valuing cultural diversity, the importance of students respecting one another, the importance of applying democratic values, the role of teachers as facilitators of inclusive learning, the creation of an equitable and welcoming school climate, the organization of events that promote cross-cultural communication, and the improvement of students' self-awareness and self-respect. Both internal and external factors have contributed to subpar implementation, with the former citing constraints on instructional time, inadequate multicultural education teacher training, and a dearth of learning resources and media; the latter citing the impact of students' social environments, an absence of ongoing extracurricular activities focused on diversity, and a lack of parental support. Overall, while the implementation of multicultural education has been carried out fairly well, it still requires strengthening in terms of teacher competence, facility support, and collaboration among the school, families, and the wider community to ensure greater effectiveness and sustainability.